3(2x-3)-3=3(x-2)+9

Simple and best practice solution for 3(2x-3)-3=3(x-2)+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2x-3)-3=3(x-2)+9 equation:



3(2x-3)-3=3(x-2)+9
We move all terms to the left:
3(2x-3)-3-(3(x-2)+9)=0
We multiply parentheses
6x-(3(x-2)+9)-9-3=0
We calculate terms in parentheses: -(3(x-2)+9), so:
3(x-2)+9
We multiply parentheses
3x-6+9
We add all the numbers together, and all the variables
3x+3
Back to the equation:
-(3x+3)
We add all the numbers together, and all the variables
6x-(3x+3)-12=0
We get rid of parentheses
6x-3x-3-12=0
We add all the numbers together, and all the variables
3x-15=0
We move all terms containing x to the left, all other terms to the right
3x=15
x=15/3
x=5

You can always share this solution

See similar equations:

| X-0,15x=4800 | | (x-10)=-99 | | 1.5=1.2y=5.7 | | 2=10-3(x+7)+5(1-x)+6x | | X=7x-23 | | 4b÷8=20b= | | 4b÷8=20 | | 4.7x+2-4x=7+2x+4 | | 3-x/3=9/2 | | n+22=72 | | 8w?12=?5 | | (10x+9)=(4x+1) | | x^2?7x+2=0 | | 11x5=8x-6 | | 5(3m-2)-9(5-2m)=4m+2(5m+1) | | 2x2=300 | | 5(3m-2)-9(5-2m)=4m+2(5m+1 | | 3x+4=5-9 | | 9/x=98/7 | | 3x+17=32;3 | | 5x+3=15x+7 | | 261=152-v | | 5x+3+15x+7=180 | | 4x+5=17;3 | | 8/x^2-1-4/x-1=2/x+1 | | 23=3/1b–2+3/4b | | (4x-25)(2x-1)=180 | | 8y+–11y+8=17 | | -13+p=-10 | | 1.5x-(6)=7.5 | | 7x+4-2x=10x+16 | | 2x?3+4x=29 |

Equations solver categories